The role of nuclear factor erythroid 2–related factor 2 (NRF2) in normal and pathological pregnancy: A systematic review - Tantengco, Ourlad Alzeus G.; de Castro Silva, Mariana [UNESP]; Shahin, Hend; Bento, Giovana Fernanda Cosi [UNESP]; Cursino, Geovanna Cristofani [UNESP]; Cayenne, Samir; da Silva, Marcia Guimarães [UNESP]; Menon, Ramkumar (Wiley, 2021)
Objective: A homeostatic balance between reactive oxygen species production and the antioxidant redox system is an important component of normal pregnancy. Nuclear Factor Erythroid 2–Related Factor 2 (Nrf2) preserves cellular homeostasis by enhancing the cell's innate antioxidant status to reduce oxidative stress and inflammatory damage to the cell during pregnancy. Active Nrf2, in the nucleus of the cell, transactivates various antioxidant genes. The objective of this systematic review was to synthesize evidence on the role of Nrf2 in various adverse pregnancy outcomes (APOs). Methods: We conducted a systematic review of the role of Nrf2 in pregnancy. Articles written in English, Portuguese, and Spanish were obtained from three different databases from inception until January 2021. The titles, abstracts and full text were reviewed independently by six reviewers. The quality of the included studies was assessed using a quality assessment tool developed to assess basic science and clinical studies. Nrf2 expression (gene and protein), functional contributions, and association with APOs were assessed. Results: A total of 747 citations were identified; 80 were retained for full review. Most studies on Nrf2 have been carried out using placental tissues and placenta-derived cells. Limited studies have been conducted using fetal membranes, uterus, and cervix. Nuclear translocation of Nrf2 results in transactivation of antioxidant enzymes, including glutathione peroxidase, hemeoxygenase-1, and superoxide dismutase in gestational cells during pregnancy. This antioxidant response maintains cellular homeostasis during pregnancy. This promotes trophoblast cell survival and prevents cell death and abnormal angiogenesis in the placenta. Excessive and insufficient Nrf2 response may promote oxidative and reductive stress, respectively. This Nrf2 dysregulation has been associated with APOs including gestational diabetes mellitus, intrauterine growth restriction, reproductive toxicity, preeclampsia, and preterm birth. Conclusion: Several studies have localized and reported an association between Nrf2's differential expression in reproductive tissues and the pathogenesis of APOs. However, a comprehensive functional understanding of Nrf2 in reproductive tissues is still lacking. Nrf2's activation and functions are complex, and therefore, current in vitro and in vivo studies are limited in their experimental approaches. We have identified key areas for future Nrf2 research that is needed to fill knowledge gaps.
Keywords: antioxidant; gestational diabetes mellitus; oxidative stress; preeclampsia; preterm birth; reproductive toxicity